State Owned Enterprises - Biba, Diana (European Journal of Economics and Business Studies, 2020)
According to OECD (2015), any corporate entity recognized by national law as an enterprise, and in which the state exercises ownership, should be considered as a State-Owned Enterprise (SOE). Although most industrialized economies are characterized by open and competitive markets firmly rooted in the rule of law, with private enterprises as the predominant economic actors yet governments continue to own and operate national commercial enterprises in key industries, making them important actors in the market, in the economy and in the society. The SOEs are an established reality world - wide but how well this reality performs is another question, that needs to be considered case by case. However, it may be concluded that when governed transparently and efficiently, SOEs can play a role in creating fairer, more competitive markets. Thus, in order to maximize their contribution to the economy and the society, SOEs should be productive and efficient.